2014
DOI: 10.3109/08880018.2014.939794
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated CD3/CD19-Depleted Peripheral Stem Cell Transplantation for Hurler Syndrome

Abstract: For patients with mucopolysaccharidosis type IH (MPS1-H; Hurler syndrome), early allogeneic hematopoietic stem cell transplantation (HSCT) is the treatment of choice. One boy and one girl aged 20.5 and 22 months, respectively, with MPS1-H received a conditioning regimen consisting of thiotepa, fludarabine, treosulfan, and ATG. Grafts were peripheral blood stem cells from unrelated donors (10/12 and 11/11 matched), that were manipulated by CD3/CD19 depletion and contained 20.3 and 28.2 × 10(6) CD34+ cells/kg bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Pediatric patients with MPS I, who received a conditioning regimen consisting of treosulfan, achieved stable hematopoietic engraftment and stable donor chimerism without GVHD. The regimen with treosulfan could be an additional option when unrelated donor HSCT is considered for a patient with MPS [33]. A pilot study of treosulfan in our facility showed the better outcomes for pediatric patients with metabolic disorders treated by HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients with MPS I, who received a conditioning regimen consisting of treosulfan, achieved stable hematopoietic engraftment and stable donor chimerism without GVHD. The regimen with treosulfan could be an additional option when unrelated donor HSCT is considered for a patient with MPS [33]. A pilot study of treosulfan in our facility showed the better outcomes for pediatric patients with metabolic disorders treated by HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric MPS patients, who received a conditioning regimen consisting of treosulfan and others, achieved stable hematopoietic engraftment and stable donor chimerism without GVHD. The regimen with treosulfan could be an additional option when unrelated donor HSCT is considered for a patient with MPS (Schwinger et al 2014 ) although the donor cell engraftment into the brain might be limited with this type of transplant. The long-term observation of HSCT with treosulfan is required.…”
Section: Advent Of Newborn Screening Programs and Future Neonatal Thementioning
confidence: 99%